EP 61. Performing deep brain stimulation and neural recordings at the same target from awake animals: A new bidirectional wireless device. Issue 9 (September 2016) - Melo-Thomas, L.; Engelhardt, A.; Thomas, U.; Hoehl, D.; Bremmer, F.; Schwarting, R.
Abstract : Although deep brain stimulation (DBS) has been proven to be an effective treatment for several neurological and psychiatric disorders, including Parkinson's disease (PD), dystonia, epilepsy, depression, and obsessive–compulsive disorder, the underlying mechanisms are still unknown. This lack of knowledge could be surmounted e.g. by employment of a suitable micro-stimulation system adapted for chronic DBS in small laboratory animals. Conventional neural recording systems restrict behavioral experiments to a flat indoor environment compatible with the cable that tethers the subject to the recording instruments. To overcome these constraints, we developed a wireless multi-channel system for brain stimulation and neuronal activity recording in freely behaving small animals. This device, which has a size and weight compatible for use in freely moving rats, can be clipped on the animal's head to a previously implanted electrode. This easy "removal" property is crucial because it enables removing or even switching the stimulator/recorder during the experiments without having to anaesthetize or to operate the animal, thus minimizing stress. The device takes extracellular recorded signals from implanted electrodes, amplifies the signals with a programmable gain main amplifier by a factor of 200 to 12800 and transmits the output by radio frequency to a transceiver up to 4 m distance. Comparable to tethered recording systems, our device is working without connection cables, and has a weight of 3.9 g (without accumulator). Stimulation electronics consists essentially of two assemblies: constant-current source and power supply. The power supply of the constant current (20–200 μA) source is biphasic, so that a voltage of 6 V is required. This allows effective stimulation and recording of neuronal signals in freely behaving animals. The present study describes the validation and in vivo implementation of this device. Our testing showed that recorded neuronal activities and stimulation of the rat inferior colliculus yields similar results as previously shown by conventional wired devices. Furthermore, the bidirectional wireless device does not restrict the animal's mobility providing a flexible method to control stimulation and neural recording under circumstances where other approaches would be difficult or impossible.